a , b ∈ R , a > b > 0 , Find the minimum of 2 a 3 + a b − b 2 3
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since a > b > 0 , we can let a = b + x , where x > 0 . Let f ( a , b ) be the expression. Then
f ( a , b ) = 2 a 3 + a b − b 2 3 = 2 ( b + x ) 3 + b x 3 ≥ 2 ( 2 b x ) 3 + b x 3 = 4 ( 2 b x ) 3 + ( 2 b x ) 2 6 By AM-GM inequality
Let u = 2 b x and g ( u ) = 4 u 3 + u 2 6 ⟹ d u d g ( u ) = 1 2 u 2 − u 3 1 2 ⟹ u = 1 , when d u d g ( u ) = 0 . Since d u d 2 g ( u ) ∣ ∣ ∣ ∣ u = 1 > 0 , min ( g ( u ) ) = g ( 1 ) = 1 0 . Therefore f ( a , b ) ≥ 1 0 and equality occurs when b = x = 2 1 and a = 2 .
minimizing 2 a 3 + ( b ) ( a − b ) 3
-> 2 a 3 + ( a ) ( b ) ( a − b ) 3 a
-> 2 a 3 + a 3 ( a − b 1 + b 1 )
by AM HM inequality, a − b 1 + b 1 > = a 4
therefore, we have to minimize 2 a 3 + a 2 1 2 .
break it into 2 2 a 3 + 2 2 a 3 + a 2 4 + a 2 4 + a 2 4 .
Applying AM GM, 2 2 a 3 + 2 2 a 3 + a 2 4 + a 2 4 + a 2 4 > = 5 × ( ( 2 2 ) 2 6 4 ) 1 / 5 Which gives \( \boxed{10}
\)
Problem Loading...
Note Loading...
Set Loading...
Note that a = ( a − b ) + b ≥ 2 ( a − b ) b , which implies that ( a − b ) b 1 ≥ a 2 4 .
Now 2 a 3 + a b − b 2 3 ≥ 2 a 3 + a 2 1 2 = 2 2 a 3 + 2 2 a 3 + a 2 4 + a 2 4 + a 2 4 ≥ 5 ( 2 5 ) 5 1 = 1 0 , where the equality holds iff a = 2 and b = 2 2 .